Study of infectious intestinal disease in England: rates in the community, presenting to general practice, and reported to national surveillance. Issue 7190 (17th April 1999) - Wheeler, Jeremy G; Sethi, Dinesh; Cowden, John M; Wall, Patrick G; Rodrigues, Laura C; Tompkins, David S; Hudson, Michael J; Roderick, Paul J
Abstract : Abstract: Objective: To establish the incidence and aetiology of infectious intestinal disease in the community and presenting to general practitioners. Comparison with incidence and aetiology of cases reaching national laboratory based surveillance. Design: Population based community cohort incidence study, general practice based incidence studies, and case linkage to national laboratory surveillance. Setting: 70 general practices throughout England. Participants: 459 975 patients served by the practices. Community surveillance of 9776 randomly selected patients. Main outcome measures: Incidence of infectious intestinal disease in community and reported to general practice. Results: 781 cases were identified in the community cohort, giving an incidence of 19.4/100 person years (95% confidence interval 18.1 to 20.8). 8770 cases presented to general practice (3.3/100 person years (2.94 to 3.75)). One case was reported to national surveillance for every 1.4 laboratory identifications, 6.2 stools sent for laboratory investigation, 23 cases presenting to general practice, and 136 community cases. The ratio of cases in the community to cases reaching national surveillance was lower for bacterial pathogens (salmonella 3.2:1, campylobacter 7.6:1) than for viruses (rotavirus 35:1, small round structured viruses 1562:1). There were many cases for which no organism was identified. Conclusions: Infectious intestinal disease occurs in 1   in 5 people each year, of whom 1 in 6 presents to a general practitioner. The proportion of cases not recorded by national laboratory surveillance is large and varies widely by microorganism.Ways of supplementing the national laboratory surveillance system for infectious intestinal diseases should be considered.